Latvia and Estonia: The Soviet Period of Economic Development - Renald H. Simonyan (Современная Европа)
The article analyses the Soviet period of Latvia and Estonia, which turned out to be very productive for their socio-economic development. In the Baltic republics, there were nо resources necessary for the development of the national economy. Latvia and Estonia were almost completely dependent on supplies from outside the region. At the same time, they had the advantage over other republics in terms of geographic position, in particular a network of seaports. The transit potential of the Baltic States was one of the main factors of preferential investment. New industrial enterprises were created, power plants, seaports, airfields were built, transport highways were laid. The processes of modernization were supported by labour migration from other republics of the USSR and subsidised by the central government. At the same time a highly qualified and skilled personnel was formed, trained both in educational institutions of Latvia and Estonia, and in leading universities in Moscow, Leningrad and other cities of the Soviet Union. Today Latvia and Estonia, along with the Czech Republic and Slovenia, occupy leading positions among the post-socialist countries of Europe in terms of socio-economic development. Based on a broad factual material, it is demonstrated that a significant contribution to their development belongs to the Soviet heritage.